Nilai Pendidikan Islam Kisah Nabi Ibrahim ‘alaihi al-salām Dalam al-Qur’an: (Kisah Penyembelihan Putra Ibrahim ‘alaihi al-salām, Ismail ‘alaihi al-salām) - Maryono Maryono (STAI Ali bin Abi Thalib Surabaya, 2019)
Al-Qur’an as a source of Islamic education, among its contents is about the stories of the Prophets in which implied the values of Islamic education which is very important and beneficial to the world of education. Among the stories of the prophets, is the story of the journey of the Prophet Ibraham ‘alaihis Salam, which is full of wisdom. His figure as a Prophet, the father of the prophets, the apostle Ulul Azmi, Khalilullah, is able to make him an example or figure of a good educator. The purpose of this research is to find out the values of Islamic education in the story of Prophet Ibrahim ‘alaihis Salam, especially in the story of the slaughtering order of his son, the prophet Ismail 'alaihis Salam. Which with these orders became the Shari'a of Sacrifice for the people of the Prophet Muhammad ṣallallāh ʿalaih wasallam. The research method used is qualitative non-interactive because the source of the data is in the form of documents, not direct data from people in their natural environment. The analysis of the data used is Content analysis, namely research that is in-depth discussion of the contents of a written information. Allah has explained the story of the slaughter of the son of the Prophet Ibrahim 'alaihis Salam, the prophet Ismail 'alaihis Salam in the Qur'an as-Shaffat verses 99-111. The values of Islamic education contained in this story are: Uluhiyah values which include aqidah values and worship values. The value of aqidah is reflected in the belief in Allah, namely the obedience of the Prophet Ibrahim and Ismail and in carrying out God's commands to slaughter his son Ismail. The value of worship is manifested in the implementation of qurban worship. The meaning implied in the implementation of Sacrifice worship is very much, including; (1) the realization of gratitude for the gift and favor of Allah, (2) Fostering a spirit of self-sacrifice, (3). Qurban teaches us to be generous, not greedy, greedy and greedy, (4) symbolically qurban educates us to kill animalistic qualities, (5) according to the meaning of harfiyah, qurban means close, meaning an effort to draw closer to God. The Insaniyah values are identified with the moral values of which are: honesty, tabligh, compassion, exemplary.